Transplantation of adult‐size kidneys in small pediatric recipients: A single‐center experience. (27th March 2019) - Muramatsu, Masaki; Mizutani, Toshihide; Hamasaki, Yuko; Takahashi, Yusuke; Itabashi, Yoshihiro; Kubota, Mai; Hashimoto, Junya; Oguchi, Hideyo; Sakurabayashi, Kei; Hyodo, Yoji; Shinoda, Kazunobu; Kawamura, Takeshi; et al.
Abstract: RTx of adult‐size kidneys presents a size mismatch in small pediatric recipients, and there are potential surgical complications. This study reveals the outcomes of intra‐ and extraperitoneal RTx in low‐weight (less than 15 kg) pediatric recipients. We studied 51 pediatric patients weighing less than 15 kg who received a living‐related donor renal transplant between 2009 and 2017. The intraperitoneal (group A, n = 24) and extraperitoneal (group B, n = 27) approaches were compared. In group A, the mean age, Ht, and weight were 3.8 ± 1.6 years, 83.7 ± 6.5 cm, 10.5 ± 1.8 kg; in group B, 5.0 ± 1.9 years, 95.3 ± 7.3 cm, and 13.0 ± 1.4 kg. Single renal artery grafts (21 in group A and 16 in group B) and double renal artery grafts (three in group A and 11 in group B) were performed. Of the patients with double renal artery transplants, one in group A and six in group B underwent ex vivo arterial reconstruction. The eGFR (mL/min/1.73 m 2 ) at 1‐week post‐transplant in group A was significantly higher than that in group B; the eGFRs at 4 weeks post‐transplant did not differ. One graft was lost in group B because of vascular thrombosis. Post‐transplant complications included ileus and transplant ureteral stenosis. There was no significant difference in 5‐year graft survival rate (group A 100%, group B 91.7%). Both transplant approaches are feasible to adapt to a size mismatch between the adult‐size donor kidney and low‐weight pediatric recipients.